2013
DOI: 10.1089/neu.2012.2392
|View full text |Cite
|
Sign up to set email alerts
|

Updating Memory after Mild Traumatic Brain Injury and Orthopedic Injuries

Abstract: Few studies have examined the trajectory of recovery of executive function (EF) after mild TBI (mTBI). Therefore, consensus has not been reached on the incidence and extent of EF impairment after mTBI. The present study investigated trajectory of change in executive memory over 3 months after mTBI on 59 right-handed participants with mTBI, as defined by Centers for Disease Control criteria, ages 14-30 years, recruited within 96 hours post-injury and tested <1 week (baseline), 1 month, and 3 months after injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…The outcome of the study is compatible with findings from other studies. However, in contrast to previous studies [1,13,16,17,19,[20][21][22][23], the MTBI patients showed no significantly reduced speed of information processing as was evaluated with the PASAT. An overview of the results of this study can be seen in Table 1.…”
Section: Cognitive Problems After Mild Traumatic Brain Injurycontrasting
confidence: 99%
See 3 more Smart Citations
“…The outcome of the study is compatible with findings from other studies. However, in contrast to previous studies [1,13,16,17,19,[20][21][22][23], the MTBI patients showed no significantly reduced speed of information processing as was evaluated with the PASAT. An overview of the results of this study can be seen in Table 1.…”
Section: Cognitive Problems After Mild Traumatic Brain Injurycontrasting
confidence: 99%
“…In MTBI patients, mild impairments in speed of information processing, (sustained, divided, focused and/or alternating) attention and (auditory-verbal and/or visuospatial) memory have been found [1,13,16,17,19,[20][21][22][23]. With regard to memory, most patients displayed deficits concerning the storage of new information into memory and/ or the reproduction of recently learned information from memory.…”
Section: Cognitive Problems After Mild Traumatic Brain Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…For a complete description of the sample and all study procedures, see Hanten and associates 29 ; only procedures relevant to the present analysis are described below. Neuropsychological measures included the Brief Visual Memory Test-Revised 30 immediate recall (BVMT-R Total), the Verbal Selective Reminding Test 31,32 including the number of words recalled after a delay (VRST Delay) and number of words continuously recalled (VSRT CLTR), and the Symbol-Digit Modalities Test 33 oral (SDMT-O) and written (SDMT-W) administrations.…”
Section: Methodsmentioning
confidence: 99%